2016
DOI: 10.1016/j.celrep.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

MyT1 Counteracts the Neural Progenitor Program to Promote Vertebrate Neurogenesis

Abstract: SummaryThe generation of neurons from neural stem cells requires large-scale changes in gene expression that are controlled to a large extent by proneural transcription factors, such as Ascl1. While recent studies have characterized the differentiation genes activated by proneural factors, less is known on the mechanisms that suppress progenitor cell identity. Here, we show that Ascl1 induces the transcription factor MyT1 while promoting neuronal differentiation. We combined functional studies of MyT1 during n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 62 publications
3
78
1
Order By: Relevance
“…This is often referred to the decrement of Notch ligand from neighboring cells (Nelson, Hodge, Bedogni, & Hevner, 2013), that results in repression of target genes through the action on corepressors recruited by RBPJ. However, recent studies suggest the possibility of cell-autonomous mechanisms to inhibit the Notch-1 program (Kawaguchi et al, 2008;Nelson et al, 2013;Vasconcelos et al, 2016). One contribution to these mechanisms can be the lowering of mSEL-1L outside the germinal niches.…”
Section: Discussionmentioning
confidence: 99%
“…This is often referred to the decrement of Notch ligand from neighboring cells (Nelson, Hodge, Bedogni, & Hevner, 2013), that results in repression of target genes through the action on corepressors recruited by RBPJ. However, recent studies suggest the possibility of cell-autonomous mechanisms to inhibit the Notch-1 program (Kawaguchi et al, 2008;Nelson et al, 2013;Vasconcelos et al, 2016). One contribution to these mechanisms can be the lowering of mSEL-1L outside the germinal niches.…”
Section: Discussionmentioning
confidence: 99%
“…Once the cells have embarked for differentiation they do not only down-regulate Notch activity but also the responsiveness of the Hes1 promoter toward NICD/RPBj transcriptional complex 24-26 . In this context, the transcriptional repressor MyT1 has recently been found to negatively regulate Hes1 expression and to counteract Notch-mediated activation of the Hes1 locus 27 . The expression of MyT1 itself is negatively coupled to Notch activity via its transcriptional activator Ascl1 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we inferred that the substantial up-regulation in late-acting stress-response gene expression in 6F; Pdx1 Cre islets was not mediated by the early-acting UPR sensor-effectors, and consequently postulated that the Myt TFs normally work to directly repress transcription of these late-stage stress-pathway genes. Supporting this hypothesis, in silico analysis and data mining of published ChIP-seq data derived from fibroblasts and neuronal progenitors (Bellefroid et al, 1996;Mall et al, 2017;Vasconcelos et al, 2016) have identified several putative Myt TF binding sites (proposed AAGTT consensus, Bellefroid et al, 1996) within 5' cis-regulatory regions of Atf4, Hspa1a, Hspa1b, HspH1, and Dnajb1 ( Figure 3B), although their significance to expression of these stress-pathway genes was not reported.…”
Section: Embryonic Inactivation Of Myt Tfs Potentiates Stress-gene Exmentioning
confidence: 89%
“…Myt1 significantly activated expression of the Hspa1a, Hspa1b, HspH1, and Atf4 reporters, but not Dnajb1. The more modest effect on Dnajb1-driven transcription could reflect the absence in our construct of an additional Myt-binding site detected at roughly -6 kbp in fibroblasts and neuronal cells (Mall et al, 2017) (Vasconcelos et al, 2016), because 5'-flanking control regions containing this putative binding site were for unknown reasons unclonable. Note that while we were probing the mechanisms for the transcriptionally repressive effects of Myt TFs on stress-pathway genes that we had detected in pancreatic  cells, these out-of-context assays in HEK293T cells showed activation not repression, which we expected based on the similar "reversals" that occurred when testing the AAGTT motifs in artificial in vitro reporter-transfection assays (Bellefroid et al, 1996;Manukyan et al, 2018;Yee and Yu, 1998).…”
Section: Myt1 Binds To Cis-regulatory Sequences Within Stress-responsmentioning
confidence: 91%
See 1 more Smart Citation